(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The successful implementation of economic, political, and socio-cultural transformations outlined by the 26th Party Congress and subsequent plenary sessions of the CPSU Central Committee was inextricably linked with the improvement of the political system of a developed socialist society, an integral element of which was the Soviet state of the whole people, its entire political mechanism. The need for an intensive study of this problem of socialist statehood is determined by the role of the Soviet state of the whole people as the main instrument for improving developed socialism, building communism and protecting the socialist state. In the conditions of mature socialism, the importance of the mechanism of the people’s state, the coordinated work and the clear interaction of all its components increased, which is a necessary condition for the effective, targeted activity of the state in the post-Soviet space in all spheres of public life, the successful fulfilment of its tasks and functions.